Uticaj sovjetske doktrine na rusku parnicu / The Impact of Soviet Doctrine on Russian Litigation - Omanović, Sanjin; Ruhotina, Anisa (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Even though the Soviet regime is the history in the context of development of the Russian civil procedural law, the studying of this epoch is necessary in order to perceive its’ impact on today’s Russian litigation. Despite the fact that nowadays’ Russian litigation is based on substantially different political, ideological and legal fundaments, it didn’t go far from the Soviet regime’s standpoint. In that regard this paper reflects on fundamental theoretical concepts of the seven most influential soviet litigation theorists, as well as some of the today’s theories. Finally, authors aim to determine to which extent has the Soviet doctrine impacted the Russian litigation in terms of prescribing legislation solutions and creating case law by the Soviet courts.